Advanced Surgical Management of Gliomas: Technological Requirements, Concept of Information-Guided Resection, and Clinical Results - Muragaki, Yoshihiro; Iseki, Hiroshi; Maruyama, Takashi; Chernov, Mikhail; Suzuki, Takashi; Yoshimitsu, Kitaro; Tamura, Manabu; Ikuta, Soko; Saito, Masayuki Nitta Taiichi; Okamoto, Jun; Takakura, Kintomo (IntechOpen, 2011)
None